2022
DOI: 10.3389/fmicb.2022.980615
|View full text |Cite
|
Sign up to set email alerts
|

Potential antifungal targets based on histones post-translational modifications against invasive aspergillosis

Abstract: As a primary cause of death in patients with hematological malignancies and transplant recipients, invasive aspergillosis (IA) is a condition that warrants attention. IA infections have been increasing, which remains a significant cause of morbidity and mortality in immunocompromised patients. During the past decade, antifungal drug resistance has emerged, which is especially concerning for management given the limited options for treating azole-resistant infections and the possibility of failure of prophylaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…It has been reported that mNGS has a sensitivity rate of 95.59% and a specificity rate of 84.6% for the diagnosis of pulmonary invasive fungal disease. 15 Therefore, mNGS is particularly useful in the diagnosis of Aspergillus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that mNGS has a sensitivity rate of 95.59% and a specificity rate of 84.6% for the diagnosis of pulmonary invasive fungal disease. 15 Therefore, mNGS is particularly useful in the diagnosis of Aspergillus infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mNGS has a sensitivity rate of 95.59% and a specificity rate of 84.6% for the diagnosis of pulmonary invasive fungal disease. 15 Therefore, mNGS is particularly useful in the diagnosis of Aspergillus infection. mNGS can comprehensively analyze pathogens, enabling universal pathogen detection of bacteria, viruses, fungi, and parasites in a single run; this has great advantages in diagnosis of mixed fungal infections.…”
Section: Discussionmentioning
confidence: 99%